2020
DOI: 10.1002/ange.202011738
|View full text |Cite
|
Sign up to set email alerts
|

Oligosilanes as Silyl Radical Precursors through Oxidative Si−Si Bond Cleavage Using Redox Catalysis

Abstract: Oligosilanes are of great interest in the fields of organic photonics and electronics. In this communication, a highly efficient visible‐light‐mediated hydrosilylation of electron‐deficient alkenes through cleavage of a trimethylsilyl‐polysilanyl Si−Si bond is explored. These reactions smoothly occur on readily available organo(tristrimethylsilyl)silanes and other oligosilanes in the presence of an IrIII‐based photo‐redox catalyst under visible light irradiation. Silyl radicals are generated through single ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 89 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…The reaction tolerates carboxylic acids with various ring sizes, cyclic or acyclic ethers and protected amines (PG = Boc (tert-butoxycarbonyl), Bac (tert-butylaminocarbonyl), Piv (pivaloyl), Cbz (carboxybenzyl)), and even drugs and peptides as nucleophiles in the context of late stage functionalisation. Finally, Studer and co-workers developed a BCB hydrosilylation reaction to give cyclobutyl silanes 68 80 . A photoredox-catalysed oxidation of disilanes generated a silyl radical, which could add to BCBs as well as electron-deficient alkenes.…”
Section: Substituted Cyclobutanes By Strain-release Ring-openingmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction tolerates carboxylic acids with various ring sizes, cyclic or acyclic ethers and protected amines (PG = Boc (tert-butoxycarbonyl), Bac (tert-butylaminocarbonyl), Piv (pivaloyl), Cbz (carboxybenzyl)), and even drugs and peptides as nucleophiles in the context of late stage functionalisation. Finally, Studer and co-workers developed a BCB hydrosilylation reaction to give cyclobutyl silanes 68 80 . A photoredox-catalysed oxidation of disilanes generated a silyl radical, which could add to BCBs as well as electron-deficient alkenes.…”
Section: Substituted Cyclobutanes By Strain-release Ring-openingmentioning
confidence: 99%
“…Jui and co-workers [79] Silanes: Studer and co-workers [80] Alkanes by dechlorination: Lin and co-workers [46] Ethers and amines by decarboxylation: Cintrat and co-workers [47] D: Umpolung BCB activation: Gryko and co-workers [48] Conditions…”
Section: N-methyl Anilinesmentioning
confidence: 99%
“…On the other hand, Studer and coworkers reported that nucleophilic silyl radicals were generated via single-electron oxidation of disilanes by Ir-based photo-redox catalysts under visible light irradiation. 21 Even though Au has a thermodynamically stable metallic state, cationic Au species with a high oxidation potential (E Au(0)/Au(I) = +1.69 V vs. SHE) 22 are known to form at the interface between their nanoparticles and metal oxides. 23 As HAADF-STEM image of Au/ZrO2 shown in Figure 2a, Au nanoparticles are highly dispersed at the surface of ZrO2 with their mean diameter of 2.9 nm.…”
Section: Pd Znmentioning
confidence: 99%
“…2, d). 57,58 A few years ago, Grubbs and coworkers developed a base-promoted silylation of C-H bonds suggesting a radical addition-dehydrogenation process (Fig. 2, e).…”
mentioning
confidence: 99%